2022
DOI: 10.1029/2021sw002915
|View full text |Cite
|
Sign up to set email alerts
|

Machine‐Learned HASDM Thermospheric Mass Density Model With Uncertainty Quantification

Abstract: Space Situational Awareness is a major focus of space agencies and private defense/technology companies worldwide. With the number of objects in low-Earth orbit (LEO) continuously growing, knowledge of future satellite/ debris positions is becoming increasingly important (Radtke et al., 2017). While there are numerous perturbations affecting the trajectories of objects, atmospheric drag is the largest source of uncertainty in the LEO region (Emmert et al., 2017;Storz et al., 2005). Our current understanding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 54 publications
1
50
0
Order By: Relevance
“…A higher noise level in the second iteration allows the estimated density to track the high‐frequency variations in the true density. During the 2003 Halloween storm, the errors in HASDM are around 20%–25% around the storm period along both CHAMP and GRACE‐A orbits (Licata, Mehta, Tobiska, & Huzurbazar, 2021). Using their machine‐learned global temperature model called EXTEMPLAR‐ML, Licata, Mehta, Wiemer, and Tobiska (2021) were able to reduce the mean density errors to 17.49% along CHAMP's orbit and 19.91% along GRACE‐A's orbit.…”
Section: Discussionmentioning
confidence: 99%
“…A higher noise level in the second iteration allows the estimated density to track the high‐frequency variations in the true density. During the 2003 Halloween storm, the errors in HASDM are around 20%–25% around the storm period along both CHAMP and GRACE‐A orbits (Licata, Mehta, Tobiska, & Huzurbazar, 2021). Using their machine‐learned global temperature model called EXTEMPLAR‐ML, Licata, Mehta, Wiemer, and Tobiska (2021) were able to reduce the mean density errors to 17.49% along CHAMP's orbit and 19.91% along GRACE‐A's orbit.…”
Section: Discussionmentioning
confidence: 99%
“… are temporal PCA coefficients and are orthogonal modes—also called basis functions. The choice order of truncation ( r = 10) was chosen from analyses in previous work as it allows for 90% of the variance to be captured and only results in % truncation error 23 , 54 . The orthogonal modes are derived through U consists of orthogonal vectors representing the modes of variability.…”
Section: Methodsmentioning
confidence: 99%
“…6 ). Licata et al found that the mean square error loss function resulted in underestimated uncertainty estimates in surrogate modeling for the HASDM dataset 23 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations